Serum Vitamin A Levels May Affect the Severity of Ocular Graft-versus-Host Disease - Tong, Jiefeng; Hu, Renjian; Zhao, Yingying; Xu, Yang; Zhao, Xiaoying; Jin, Xiuming (Frontiers in Medicine, 2017)
Allogeneic hematopoietic stem cell transplantation (HSCT) is used to treat a variety of acquired and congenital hematological disorders. However, allogeneic HSCT can give rise to GVHD, a significant cause of morbidity and mortality in allogeneic HSCT recipients. Ocular manifestations occur in up to 80% of chronic GVHD patients. In our cases, the diagnosis of vitamin A deficiency was suspected for GVHD patients. Serum vitamin A measurements were conducted to confirm clinical suspicions. Our study revealed significant decrease in serum levels of vitamin A in patients with chronic liver GVHD. Although there have been many studies evaluating ocular manifestations in patients with GVHD, the present study is, to our knowledge, the first to report an association between vitamin A and ocular manifestations of graft-versus-host disease in humans. Our data suggest that vitamin A deficiency affects the severity of ocular GVHD in adults.